Revisiting the Darwin wasp genus Epelaspis Townes, 1970 (Hymenoptera: Ichneumonidae: Phygadeuontinae): five new species, new records and a key to Neotropical species - Lima, Adriane G. M.; Pádua, Diego G.; Araujo, Rodrigo O.; Mazariegos, Luis A.; Fernandes, Daniell R. R. (Zootaxa, 2024)
The Darwin wasp genus Epelaspis Townes, 1970 (Hymenoptera: Ichneumonidae: Phygadeuontinae) is studied in some countries of South America. We recorded the genus for the first time in Colombia, and five new species are described: Epelaspis boteroi Lima & Fernandes, sp. nov., Epelaspis constantinoi Lima & Fernandes, sp. nov., Epelaspis lulo Lima & Fernandes, sp. nov., Epelaspis tavoi Lima & Fernandes, sp. nov., and Epelaspis wagneri Lima & Fernandes, sp. nov.. Furthermore, E. anorus Townes, 1970 is newly documented for Brazil, while the geographic ranges of E. renatoi Graf & Kumagai, 1996 and E. ketiae Graf & Kumagai, 1996 are extended within the country. Digital images, maps, and a key to Neotropical Epelaspis species are provided.